2021
DOI: 10.1101/2021.06.29.450402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AUTS2 controls neuronal lineage choice through a novel PRC1-independent complex and BMP inhibition

Abstract: Despite a prominent risk factor for Neurodevelopmental disorders (NDD), it remains unclear how Autism Susceptibility Candidate 2 (AUTS2) controls the neurodevelopmental program. Our studies investigated the role of AUTS2 in neuronal differentiation and discovered that AUTS2, together with WDR68 and SKI, forms a novel protein complex (AWS) specifically in neuronal progenitors and promotes neuronal differentiation through inhibiting BMP signaling. Genomic and biochemical analyses demonstrated that the AWS comple… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Subsequently, WDR68 was identified as an additional component of the AUTS2-containing ncPRC1 complex ( Wang et al, 2018 ). On the other hand, two groups have reported that AUTS2-FL interacts with ncPRC1, but AUTS2-C does not ( Geng et al, 2021 ; Monderer-Rothkoff et al, 2021 ). In a study of mutations in AUTS2 syndrome, the interaction of AUTS2 with P300 in HEK 293 cells was found to be disrupted by mutations involving the HX repeat ( Liu et al, 2021 ).…”
Section: Molecular Functions and Interactions Of Auts2 Proteinmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequently, WDR68 was identified as an additional component of the AUTS2-containing ncPRC1 complex ( Wang et al, 2018 ). On the other hand, two groups have reported that AUTS2-FL interacts with ncPRC1, but AUTS2-C does not ( Geng et al, 2021 ; Monderer-Rothkoff et al, 2021 ). In a study of mutations in AUTS2 syndrome, the interaction of AUTS2 with P300 in HEK 293 cells was found to be disrupted by mutations involving the HX repeat ( Liu et al, 2021 ).…”
Section: Molecular Functions and Interactions Of Auts2 Proteinmentioning
confidence: 99%
“…Importantly, the HX repeat encompasses the alternative tss for AUTS2-C, and indeed a small deletion in the HX repeat was found to eliminate expression of AUTS2-C ( Martinez-Delgado et al, 2021 ). Significantly, most of the above-mentioned AUTS2-protein interactions and disruptions were studied in HEK cells after AUTS2 overexpression ( Gao et al, 2014 ; Wang et al, 2018 ; Geng et al, 2021 ), or in yeast two-hybrid assays ( Monderer-Rothkoff et al, 2021 ). Further studies are needed to confirm that AUTS2 interacts with proteins such as PCGF3/5, RING1B, and P300 at physiological levels in cortical neurons in vivo .…”
Section: Molecular Functions and Interactions Of Auts2 Proteinmentioning
confidence: 99%
See 3 more Smart Citations